La libertad de expresión artística como derecho fundamental - Valicenti, Ezequiel Andrés (2015)
The paper deals with the concept and structure of constitutional rights, according to the developments of Robert Alexy. It tries to demonstrate the usefulness of this theory to explore the contours of each of the constitutional rights. Specifically, the work seeks to answer the question about if should protect specially freedom of speech when the expressed is an artistic expression. From the constitutional rules and court precedents, identifies iusfundamentals reason which allowing upholds the existence of a right of artistic speech. Later his juridical protection is analyzed, which is not satisfy whit the alone abstention to interference by the state, and requires further specific rights provision